Caracterização da vulnerabilidade relacionada a síndromes respiratórias graves nos municípios da Região Metropolitana do Vale do Paraíba e Litoral Norte de São Paulo - Bosque, Rodrigo Raupp [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Desde o final de 2019 até os dias atuais, todo o planeta tem sido significativamente impactado pela pandemia COVID-19 (Corona Virus Desease-2019), causada pelo SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2), com impactos em diversos setores, como saúde, economia, educação e emprego. A gestão desse tipo de epidemia está inserida na tipologia do desastre biológico e exige ações integradas em diversas áreas do conhecimento. Assim, para combater e prevenir futuras epidemias de síndromes respiratórias agudas graves (SARS), é necessário, entre outros esforços, identificar as vulnerabilidades populacionais nos diferentes níveis de divisão política. Nesse contexto, o presente trabalho propõe um índice de vulnerabilidade que permite contextualizar os municípios da Região Metropolitana do Vale do Paraíba e Litoral Norte de São Paulo (RMVPLN), utilizando técnicas de geoprocessamento em Sistema de Informações Geográficas (SIG) que possam subsidiar tomadores de decisão na gestão e nas ações de enfrentamento aos impactos de tal desastre biológico.

Since the end of 2019 to the present day, the entire planet has been significantly impacted by the COVID-19 (Corona Virus Desease-2019) pandemic, caused by the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2), with impacts on several sectors, such as health, economy, education, and employment. The management of this kind of epidemic is inserted in the biological disaster typology and demands integrated actions in several areas of knowledge. Thus, to combat and prevent future epidemics of severe acute respiratory syndromes (SARS), it is necessary, among other efforts, to identify the population vulnerabilities at different political division levels. In this context, the present work proposes a vulnerability index which allows to describe the municipalities in the Paraíba Valley and North Coast of São Paulo Metropolitan Region, demanding geoprocessing techniques in Geographic Information System (GIS) that can subsidize decision makers to take actions to manage and to cope with the impacts of such biological disaster.
Vulnerability characterization related to severe respiratory syndromes in the Paraíba Valley and North Coast of the State of São Paulo Metropolitan Region municipalities
Keywords: SARS; Covid-19; Vulnerabilidade; Desastres biológicos; Geotecnologia; Índice de vulnerabilidade; Sars; Covid-19; Vulnerability; Biological disasters; Geotechnology; Vulnerability index